IDENTITAS ARSITEKTUR RUKO TIONGHOA DI INDRAMAYU DAN JAMBLANG: KAJIAN PERBANDINGAN WARISAN ARSITEKTUR PECINAN: IDENTITAS ARSITEKTUR RUKO TIONGHOA DI INDRAMAYU DAN JAMBLANG: KAJIAN PERBANDINGAN WARISAN ARSITEKTUR PECINAN - yudita royandi; krismanto kusbiantoro; elizabeth susanti; leonardo (Universitas Telkom, 2026)
Abstract : Chinese settlements along the northern coast of Java developed through maritime trade networks that shaped the shophouse typology as a hybrid of residential and commercial functions. Jamblang and Indramayu are two coastal towns in West Java that share a similar history of Chinese migration but exhibit different conditions regarding their shop houses. This study aims to compare the characteristics and transformation of Chinese shophouses in Indramayu and Jamblang in order to understand their divergent developmental trajectories within the framework of socio-economic resilience and diaspora architectural conservation. The research employs a descriptive qualitative approach using comparative case studies. Data were collected through field observation, visual documentation, measured drawings, and limited interviews, and analyzed based on variables including mass composition, façade design, functional adaptation, and spatial connectivity to street corridors. The findings reveal that both locations retain the fundamental courtyard-based shophouse typology. However, Indramayu demonstrates greater continuity through gradual functional adaptation and sustained integration with the commercial activities along Jalan Cimanuk. In contrast, Jamblang exhibits façade fragmentation and declining visual integrity due to infrastructural pressures and weakening local economic conditions. The study highlights that the sustainability of diaspora architecture depends not solely on formal preservation but on functional adaptability and spatial distribution within the urban fabric. These findings contribute to the development of heritage conservation strategies grounded in economic resilience and typological adaptability in coastal towns. Keywords: Chinese shophouse, diaspora architecture, adaptive reuse, heritage resilience, coastal Java